2015
DOI: 10.1093/jxb/erv464
|View full text |Cite
|
Sign up to set email alerts
|

An A20/AN1-type zinc finger protein modulates gibberellins and abscisic acid contents and increases sensitivity to abiotic stress in rice (Oryza sativa)

Abstract: The plant hormones gibberellins (GA) and abscisic acid (ABA) play important roles in plant development and stress responses. Here we report a novel A20/AN1-type zinc finger protein ZFP185 involved in GA and ABA signaling in the regulation of growth and stress response. ZFP185 was constitutively expressed in various rice tissues. Overexpression of ZFP185 in rice results in a semi-dwarfism phenotype, reduced cell size, and the decrease of endogenous GA3 content. By contrast, higher GA3 content was observed in RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 62 publications
4
54
0
1
Order By: Relevance
“…AN1/A20-like Zinc finger family proteins are evolutionarily conserved regulatory components in eukaryotic signaling circuits. In addition, the physiological functions of plant A20/AN1-ZnF family proteins have been implicated in various abiotic and biotic stress responses48.…”
Section: Discussionmentioning
confidence: 99%
“…AN1/A20-like Zinc finger family proteins are evolutionarily conserved regulatory components in eukaryotic signaling circuits. In addition, the physiological functions of plant A20/AN1-ZnF family proteins have been implicated in various abiotic and biotic stress responses48.…”
Section: Discussionmentioning
confidence: 99%
“…ZFPs are also involved in gibberellins (GA) signaling in the regulation of the stress response. Transgenic plants overexpressing the ZFPs OsDOG (Liu et al, 2011) and ZFP185 (Zhang Y. et al, 2016) displayed a reduced GA content, dwarf phenotypes and sensitivity to abiotic stress. However, plants overexpressing BBX24 (Yang et al, 2014) also showed reduced GA content, but plants expressing BBX24 showed normal growth phenotype and enhanced salt and drought stress tolerance (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of ABA-related marker gene expression in Arabidopsis suggested that GmZFP3 might be involved in the ABA-dependent pathway during the drought stress response. OsDOG and ZFP185 also play negative roles in abiotic stress tolerance (Liu et al, 2011; Zhang Y. et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Past research suggests that OSISAP11 interacts with the rice receptor-like cytoplasmic kinase OSIRLCK253 and improves drought and salt stress tolerance in transgenic Arabidopsis (Giri et al, 2011). In addition, the rice A20/AN1-type zinc finger protein ZFP185 is involved in GA and abscisic acid (ABA) signaling, which regulates growth and stress responses (Zhang et al, 2016). Recent studies have associated SAP proteins with roles including ubiquitination, redox sensing, and regulation of gene expression under abiotic stress conditions (Strƶher et al, 2009;Ben-Saad et al, 2012a, 2012bKang et al, 2013).…”
mentioning
confidence: 99%